Response to a large rotavirus outbreak on South Tarawa, Kiribati, 2013 - Teanibuaka Tabunga; Maryanne Utiera; Rosemary Tekoaua; Tebikau Tibwe; Teatao Tira; Tebuka Toatu; Sala Elbourne Duituturaga; Eric Nilles; Adam Craig (World Health Organization Regional Office for the Western Pacific, 2014)
Introduction: In July 2013, during annual independence celebrations in Kiribati, staff at Tungaru Central Hospital on South Tarawa reported an increase in children presenting with severe diarrhoea. This report describes the outbreak investigation, findings and response. Method: After notification of the outbreak, all health facilities on South Tarawa began reporting cases of acute diarrhoea and/or vomiting through the early warning syndromic surveillance system on a daily basis. Community awareness was raised and the public was encouraged to present to a health facility if ill with acute gastroenteritis. Specimens were collected and sent for laboratory testing. Results: Between 10 and 24 July 2013, 1118 cases of gastroenteritis were reported; 103 were hospitalized and six died. The median age of cases was one year (range: 0-68 years); 93.4% were aged less than five years. Rotavirus was identified in 81% of specimens tested. The outbreak response included enhanced surveillance, community education, clinical training and changes to in-hospital patient management for infection control. Discussion: This outbreak was the largest diarrhoea outbreak in Kiribati in five years. Factors that may have contributed to the magnitude and severity of the outbreak included high household density, inadequate sanitation infrastructure and a mass gathering - all increasing the chance of transmission - as well as limited clinical response capacity. The current outbreak highlights the importance of clinical management to minimize severe dehydration and death. Rotavirus vaccination should be considered as an adjunct to other comprehensive enteric disease control measures as recommended by the World Health Organization.